Augmentative and Alternative Communication in the Context of Dramatic Storytelling: A Single-Case Study of a Pre-schooler With a Cochlear Implant - Wu, Jiaojiao; Xie, Yuhan (Frontiers in Education, 2022)
This single-case study of a preschooler with a cochlear implant aimed to integrate an AAC intervention with dramatic storytelling activities to improve the participant’s receptive and expressive language ability and communication skills as a means to address her communication needs. The researcher developed a functional communication image-text vocabulary list of 50 items with five categories: people, social interactions, animals, colors, and frequently used verbs. The intervention was conducted during the regular school day in the corner of a regular classroom three days a week for six weeks. This study demonstrated that AAC developed during dramatic storytelling activities helped the participant to improve the effectiveness of functional communication vocabulary learning and increase the frequency of oral language communication. Group dramatic storytelling provides opportunities for learning through peer imitation during naturally occurring activities as well as ones for intentional and systematic AAC instruction during activities.